(untitled) (BIS Humanities and Social Science, 2026)
This study evaluates the application of a Participatory Design (PD) approach to map the creative economic potential of Bojongmalaka Village, a peri-urban community in Bandung Regency, during the 2025 calendar year. Funded by Telkom University, the research utilizes a qualitative framework—comprising in-depth interviews, focus group discussions, and field observations—to identify latent creative assets and catalyze community agency. The findings reveal a robust foundation of traditional handicrafts (bamboo and loom weaving), performing arts, and culinary traditions, supported by a significant skill base where 60% of residents possess traditional craft expertise and 40% express strong interest in contemporary design. The significance of the participatory methodology is evidenced by a transformative shift in local ownership: 75% of participants reported a heightened sense of accountability for their local economy following the process. By moving beyond extractive data collection to a co-creation model, the study demonstrates that PD ensures higher data accuracy and fosters the long-term sustainability of economic outcomes. This approach bridges the critical gap between traditional heritage and modern market demands, transforming undocumented cultural capital into a structured driver of growth. This synthesis of community expertise and strategic mapping provides the necessary empirical foundation for the situational analysis and strategic imperatives that follow.